"I can see fine": patient knowledge of eye care. (17th May 2018) - Irving, Elizabeth L.; Sivak, Alisa M.; Spafford, Marlee M.
Abstract: Purpose: To learn more about the perceptions and attitudes toward eye care of members of the public — in particular, their knowledge of the purpose, components and providers of eye examinations, their ability to self‐monitor ocular status and their awareness of major sight threatening eye conditions. Methods: This study used the qualitative research strategy, grounded theory. Participants were recruited via poster and social media. Two researchers, one with optometric knowledge and one without, moderated seven 60‐ to 90‐min, semi‐structured focus group discussions, which were audiotaped and transcribed. Participants also completed a short demographic questionnaire. Three researchers employed constant comparative coding strategies to identify common themes within the focus group transcripts. The number of participants represented by identified themes were tracked and themes were listed in order of decreasing frequency. Results: Focus groups included 25 participants (nine male, 16 female), ranging in age from 18 to 71 years (mean: 41.7). Five themes related to eye care awareness were identified: eye examination purpose, test procedure identification, eye care professional roles, asymptomatic eye disease awareness, and significant eye disease awareness. Perceived eye examination purposes were vision/prescription priority with some eye health knowledge, comprehensive evaluation of visual system, and vision/prescription only. Most participants who responded could correctly identify the use of an eye chart and a phoroptor; fewer were able to do the same for a direct ophthalmoscope and slit lamp biomicroscope. Less than a quarter of participants could accurately identify the roles of all three major eye care providers. Trauma was the most commonly mentioned risk for vision loss, followed by diabetes and infection. Participants' knowledge appeared most often to have been obtained from personal experience rather than as the result of any systematic educational initiative. Conclusions: This study found notable gaps in knowledge of eye care and sight risks. If these gaps result in fewer eye examinations, they potentially contribute to increased risk of vision loss due to later stage detection. The results provide motivation for further study and development of effective public health education strategies.